Reducing Anxiety and Shyness for Oral Interaction Improvement in a Cooperative Learning Environment - Robayo Guerrero, Jorge Orlando (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This article reports on the investigation carried out at rural school in Ubaté (Cundinamarca). Participants were sixteen English students. The aim of the study was to explore how cooperative learning reduces ninth graders’ anxiety and shyness in the English classes. In order to achieve this objective, an action research study was conducted. Interviews, teacher’s diary and workshops were used for data collection. The main findings suggested that after five workshops anxiety and shyness’ signs have reduced when students were cooperative to interact orally. In addition, cooperative learning was an effective tool not just to reduce anxiety and shyness, but also to involve them in their own English learning process, English learning